2007
DOI: 10.1111/j.0908-8857.2007.03979.x
|View full text |Cite
|
Sign up to set email alerts
|

Are parametric models suitable for estimating avian growth rates?

Abstract: For many bird species, growth is negative or equivocal during development. Traditional, parametric growth curves assume growth follows a sigmoidal form with prescribed inflection points and is positive until asymptotic size. Accordingly, these curves will not accurately capture the variable, sometimes considerable, fluctuations in avian growth over the course of the trajectory. We evaluated the fit of three traditional growth curves (logistic, Gompertz, and von Bertalanffy) and a nonparametric spline estimator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Previous methodological suggestions for studies of avian growth have largely focused on the appropriateness of different nonlinear functions (e.g. logistic, Gompertz, von Bertalanffy, and Richards functions; Starck and Ricklefs 1998, Brown et al 2007, Tjorve and Tjorve 2010), but have not discussed how these functions may be altered to test specific hypotheses. Our study illustrates how to incorporate parameters that estimate the difference between two groups in the growth rate constant, asymptotic mass, or inflection point.…”
Section: Discussionmentioning
confidence: 99%
“…Previous methodological suggestions for studies of avian growth have largely focused on the appropriateness of different nonlinear functions (e.g. logistic, Gompertz, von Bertalanffy, and Richards functions; Starck and Ricklefs 1998, Brown et al 2007, Tjorve and Tjorve 2010), but have not discussed how these functions may be altered to test specific hypotheses. Our study illustrates how to incorporate parameters that estimate the difference between two groups in the growth rate constant, asymptotic mass, or inflection point.…”
Section: Discussionmentioning
confidence: 99%
“…Fitting such regression models to growth data yields a number of parameter values and derived measurements used to discuss this type of growth. Regression models fitted to avian growth data have traditionally been the three‐parameter logistic, Gompertz and von Bertalanffy models (Ricklefs , , Brown et al , Tjørve and Tjørve ), which all belong to the Richards‐model family, meaning that they are all special cases of the four‐parameter Richards model. This is so because any of the three‐parameter models can be achieved by fixing the exponent in a Richards model to a specific value (see Tjørve and Tjørve and for specifics).…”
mentioning
confidence: 99%
“…Because this method relies on strict assumptions about the data, and growth data tend to violate these test assumptions, Jacknifed standard errors are sometimes calculated instead of the usual standard errors (Schekkerman et al 1998a, b, Pearce-Higgens and Yalden 2002, Ross et al 2012. Alternative curve-fitting methods used in bird-growth analysis include mixed models (Sofaer et al 2013, Aldredge 2015, nonparametric spline estimators (Aggrey 2002, Brown et al 2007, and robust regression (Tjørve et al 2007b(Tjørve et al , 2009b, which relax some of the assumptions about the data.…”
mentioning
confidence: 99%
“…Bauchau (1997) found that mite densities did not directly influence body mass in Pied Flycatchers (Ficedula hypoleuca) and suggested that parental quality may have been influencing nestling growth. Second, mite densities were estimated at day 23, and finding no correlation between day 10 nestling (Brown et al 2007). After reaching a maximum body mass, parents often reduce nestling provisioning to induce fledging, resulting in a decrease of body mass (Lemel 1989).…”
Section: Discussionmentioning
confidence: 98%